Thyroid autoimmunity in children with coeliac disease: a prospective survey. Issue 11 (23rd August 2011) - Diamanti, Antonella; Ferretti, Francesca; Guglielmi, Rinaldo; Panetta, Fabio; Colistro, Franco; Cappa, Marco; Daniele, Antonella; Basso, Maria-Sole; Noto, Cristian; Crisogianni, Massimo; Castro, Massimo
Abstract : Background: Thyroid autoimmunity (TA) is often associated with coeliac disease (CD). Objective: To evaluate, in children and adolescents with CD on a gluten-free diet (GFD): (1) the prevalence of TA; (2) the impact of TA on growth and the need for L-thyroxine (L-T4) treatment, during a longitudinal survey. Method: Between January and December 2005, 545 patients with CD, prospectively followed up until December 2007, and 622 controls were screened for TA. Antithyroperoxidase and antithyroglobulin antibodies were assayed and, if positive, serum free tri-iodothyronine, free thyroxine and thyroid-stimulating hormone (TSH) assays and thyroid ultrasound were performed. L-T4 was started if TSH was >5.5 mU/ml at two successive measurements. Results: There was no significant difference in TA prevalence between patients with CD on a GFD (10%) and controls (8.2%). Duration of GFD differed significantly in coeliac patients with TA in comparison with those without TA (7.9±0.9 and 10.2±0.3 years, p<0.001), but no significant difference was found for weight and height gain (1.8±1.0 vs 3.7±1.5 and 2.1±1.2 kg/year vs 4.0±1.1 cm/year, respectively). At the end of the follow-up an increase of 7% in the prevalence of patients with CD with TA requiring L-T4 was found. Conclusions: TA seems no more common in paediatric and adolescent patients with CD on a GFD than in controls; its clinical evolution does not seem to impact on growth. Therefore, a long-term regular screening programme for thyroid disease may not be necessary for all patients with CD on a GFD, but only for those who are suspected of having thyroid diseases.